Beyond TNBC: Repositioning of Clofazimine Against a Broad Range of Wnt-Dependent Cancers - Xu, Jiabin; Koval, Alexey; Katanaev, Vladimir L. (Frontiers in Oncology, 2020)
Wnt signaling plays key roles in oncogenic transformation and progression in a number of cancer types, including tumors in the breast, colon, ovaries, liver, and other tissues. Despite this importance, no therapy targeting the Wnt pathway currently exists. We have previously shown that the anti-mycobacterium drug clofazimine is a specific inhibitor of Wnt signaling and cell proliferation in triple-negative breast cancer (TNBC). Here, we expand the applicability of clofazimine to a set of other Wnt-dependent cancers. Using a panel of cell lines from hepatocellular carcinoma, glioblastoma, as well as colorectal and ovarian cancer, we show that the efficacy of clofazimine against a given cancer type correlates with the basal levels of Wnt pathway activation and the ability of the drug to inhibit Wnt signaling in it, being further influenced by the cancer mutational spectrum. Our study establishes the basis for patient stratification in the future clinical trials of clofazimine and may ultimately contribute to the establishment of the Wnt pathway-targeted therapy against a diverse set of cancer types relying on the oncogenic Wnt signaling.